Mechanical properties of Au foams under nanoindentation - Ruestes, Carlos Javier (2018)
Nanoscale metallic foams display mechanical properties which make them attractive for a variety of technological applications. We report simulated nanoindentation tests for a model polycrystalline nanoporous gold structure with 11 nm mean filament diameter and 35 nm average grain size, comparable to foams produced by dealloying. Hardness, plasticity mechanisms, the extension of the plastic zone and the applicability of several scaling laws are discussed. Plasticity occurs at the nodes mainly and is dominated by nucleation of dislocations at the atomic steps of the ligament surfaces, in a dislocation accumulation scenario. Shockley partials, perfect dislocations, Hirth partials, Lomer-Cottrel locks and twins were identified. Grain boundary sliding appears to play a minor role in deformation at the indentation rates used. Several scaling laws are tested and their results and applicability are discussed based on the structural parameters of the foam and the deformation mechanisms identified.